Evidence of past sea level change and the formation of recent coastal alluvial deposits in Peninsular Malaysia - Yee, Thien Seng, Ir. (The Institution of Engineers, Malaysia (IEM), 2019)
Link to publisher’s homepage at https://www.myiem.org.my/